Geometric Morphometric Analysis of Forewings of Apis mellifera Linnaeus, 1758 (Hymenoptera: Apidae) Populations in Thailand - Buala , Siripan; Sopaladawan, Piyamas Nanork (Tropical Natural History, 2022)
Apis mellifera beekeeping in Thailand started in the 1970s and since then has spread throughout the country. There is little information on diversity, especially morphological diversity, of these species in Thailand. The objective of this study was to examine variation among A. mellifera populations in Thailand based on geometric morphometrics of forewings. We collected A. mellifera worker bees of 160 colonies from 25 apiaries throughout Thailand. Forewing shape variation was examined based on 19 landmark coordinates. The results showed high wing morphological variation. Apis mellifera samples from Thailand were found to belong to 5 distinct groups, which were further supported by a hierarchical cluster analysis. In the size analysis, the honey bees in 5 morphotypes differed significantly in wing centroid size (p < 0.0001). Canonical variate analysis (CVA) revealed 5 distinct groups with significance in all groups (P < 0.001), and a high rate of correct classification based on a cross-validation test (85.63%) was found. Our study provided information on morphological diversity of A. mellifera in Thailand and asserts that forewing geometric morphometrics is a simple, reliable, inexpensive method that is sufficient for determination of morphological diversity of this species.